2014
DOI: 10.1371/journal.pone.0097330
|View full text |Cite
|
Sign up to set email alerts
|

High Metastaticgastric and Breast Cancer Cells Consume Oleic Acid in an AMPK Dependent Manner

Abstract: Gastric cancer and breast cancer have a clear tendency toward metastasis and invasion to the microenvironment predominantly composed of adipocytes. Oleic acid is an abundant monounsaturated fatty acid that releases from adipocytes and impinges on different energy metabolism responses. The effect and underlying mechanisms of oleic acid on highly metastatic cancer cells are not completely understood. We reported that AMP-activated protein kinase (AMPK) was obviously activated in highly aggressive carcinoma cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 37 publications
2
60
0
1
Order By: Relevance
“…Furthermore, palmitate treatment significantly induced the phosphorylation of AMPK, ACC, and p53, increased the expression of p21, and decreased the phosphorylation of mTOR (Figure D). In contrast, oleate treatment decreased total protein levels of AMPK, ACC, and p53 and p21, and increased total mTOR levels, as previously reported, and as such, levels of phosphorylated form of AMPK, ACC, and p53 were decreased, and levels of phosphorylated form of mTOR were increased (Figure D). A simultaneous stimulation with palmitate and oleate consistently showed that each of these 2 LCFAs antagonizes the effects of the other (Figure A through D).…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, palmitate treatment significantly induced the phosphorylation of AMPK, ACC, and p53, increased the expression of p21, and decreased the phosphorylation of mTOR (Figure D). In contrast, oleate treatment decreased total protein levels of AMPK, ACC, and p53 and p21, and increased total mTOR levels, as previously reported, and as such, levels of phosphorylated form of AMPK, ACC, and p53 were decreased, and levels of phosphorylated form of mTOR were increased (Figure D). A simultaneous stimulation with palmitate and oleate consistently showed that each of these 2 LCFAs antagonizes the effects of the other (Figure A through D).…”
Section: Resultssupporting
confidence: 87%
“…These cells also show upregulation of their β-oxidation related genes and repression of the de novo lipogenesis genes [51]. This is in accordance with other studies showing that the sole overexpression of group X sPLA 2 in cultured pre-adipocyte cells results in decreased transcription of genes encoding for lipogenic proteins such as SREBP-1c, fatty acid synthase or PPARγ [141]. Inhibition of fatty acid β-oxidation with etomoxir also reduces LD formation in response to group X sPLA 2 , highlighting the seemingly odd circumstance that anabolic -neutral lipid formation and storage in LD-and catabolic -β-oxidation of fatty acids-processes take place simultaneously.…”
Section: Other Spla 2 Rolessupporting
confidence: 91%
“…OA showed a biphasic stimulation (at 0.9 μM) followed by an inhibition at 3.5–9 μM in MDA‐MB‐231 cells [Rose and Connolly, ]. On the other hand, treatment of MDA‐MB‐231 cells with 400 μM BSA‐bound oleic acid increased cell viability and stimulated OCR in without affecting MCF‐7 cells [Li et al, ].…”
Section: Discussionmentioning
confidence: 99%